Electrochemical oxidation of nitrogen towards direct nitrate production on spinel oxides - Dai, Chencheng (2023)
Nitrates are widely used as fertilizer and oxidizing agents. Commercial nitrate production from nitrogen involves high-temperature-high-pressure multi-step processes. Therefore, an alternative nitrate production method under ambient environment is of importance. Herein, an electrochemical nitrogen oxidation reaction (NOR) approach is developed to produce nitrate catalyzed by ZnFexCo2−xO4 spinel oxides. Theoretical and experimental results show Fe aids the formation of the first N−O bond on the *N site, while high oxidation state Co assists in stabilizing the absorbed OH− for the generation of the second and third N−O bonds. Owing to the concerted catalysis, the ZnFe0.4Co1.6O4 oxide demonstrates the highest nitrate production rate of 130±12 μmol h−1 gMO−1 at an applied potential of 1.6 V versus the reversible hydrogen electrode (RHE).